Quantifying through Ex Post Assessments the Micro-Level Impacts of Sovereign Disaster Risk Financing and Insurance Programs - de Janvry, Alain (World Bank, Washington, DC, 2015)
Uninsured natural disasters can have devastating effects on human welfare and economic growth, particularly in developing countries where large segments of the population are in poverty and government resources and capacity to assist in relief, recovery, and reconstruction are limited. Therefore there is interest in exploring how these countries can design and implement disaster relief financing and insurance programs. This paper discusses four aspects of the microeconomics of disaster relief financing and insurance programs that are important for the ex post impact evaluation of such programs: (1) use of game setups to analyze the private willingness-to-pay for disaster protection through risk transfer or risk retention instruments; (2) use of ex post analysis of existing disaster relief financing and insurance schemes (such as Mexico’s programs) to analyze the willingness to provide political support to such schemes; (3) use of ex post analysis of existing schemes to analyze not only ex post coping with shock, but also the ex ante risk management impact of disaster relief financing and insurance schemes, with the expectation that the latter can have a large effects on growth; and (4) use of mainly global data to do ex post impact analysis of natural disasters and the resilience-enhancing value of disaster relief financing and insurance schemes (examples exist for the disaster-impact relationship that can be extended to the role of disaster relief financing and insurance in risk reduction, coping with shock, and risk management). The paper proposes concrete research projects to pursue the analysis of these four dimensions of micro-level impacts of disaster relief financing and insurance.